Key defatting tissue pretreatment protocol for enhanced MALDI MS Imaging of peptide biomarkers visualization in the castor beans and their attribution applications - Qin, Luyuan; Han, Junshan; Wang, Chuang; Xu, Bin; Tan, Deyun; He, Song; Guo, Lei; Bo, Xiaochen; Xie, Jianwei (Frontiers in Plant Science, 2022)
Castor bean or ricin-induced intoxication or terror events have threatened public security and social safety. Potential resources or materials include beans, raw extraction products, crude toxins, and purified ricin. The traceability of the origins of castor beans is thus essential for forensic and anti-terror investigations. As a new imaging technique with label-free, rapid, and high throughput features, matrix-assisted laser desorption ionization mass spectrometry imaging (MALDI-MSI) has been gradually stressed in plant research. However, sample preparation approaches for plant tissues still face severe challenges, especially for some lipid-rich, water-rich, or fragile tissues. Proper tissue washing procedures would be pivotal, but little information is known until now. In this paper, we developed a comprehensive tissue pretreatment protocol for castor beans containing plenty of lipids that were fragile when handled. A modified six-step washing procedure was chosen as the most critical parameter regarding the MSI visualization of peptides in all eight washing procedures aimed at removing lipids. We then constructed a robust MALDI-MSI method to enhance the detection sensitivity of defense peptides, Ricinus communis biomarkers (RCBs) in castor beans. The method was further applied to visualize and quantify the RCBs in castor bean tissue sections from nine different geographic sources from China, Pakistan, and Ethiopia. Multivariate statistical models, including deep learning network, revealed a valuable classification clue concerning nationality and altitude.